To Russia with Love? The Impact of Sanctions on Regime Support - Robert Gold; Julian Hinz; Michele Valsecchi (Center for Economic Studies and ifo Institute (CESifo), 2024)
Do economic sanctions affect internal support of sanctioned countries' governments? To answer this question, we focus on the sanctions imposed on Russia in 2014 and identify their effect on voting behavior in both presidential and parliamentary elections. On the economic side, the sanctions significantly hurt Russia's foreign trade — with regional variance. We use trade losses caused by the sanctions as measure for regional sanctions exposure. For identification, we rely on a structural gravity model that allows us to compare observed trade flows to counterfactual flows in the absence of sanctions. Difference-in-differences estimations reveal that regime support significantly increases in response to the sanctions, at the expense of voting support of Communist parties. For the average Russian district, sanctions exposure increases the vote share gained by President Putin and his party by 13 percent. Event studies and placebo estimations confirm the validity of our results.
Keywords: F12; F14; F15; 330; economic sanctions; voting behaviour; gravity estimation; rally-around-the-flag